Transformative Cyber Marketing: Fostering Regional Growth and Engagement - Nana Storada Dwi Martadi; Mohamad Sidiq; Inaya Sari Melati (Human Behavior and Emerging Technologies)
This study is aimed at formulating a contemporary regional cyber marketing model with a focus on endorsing local products and events in Semarang City, Indonesia. Utilizing the Star Model by Galbraith, the research involved 44 stakeholders in extensive interviews. Employing social network analysis (SNA) through the Net-Map tool, the study introduced an innovative cyber marketing approach, labeled as Semarang Cyber Marketing (SCyMark), designed to meet the unique requirements of the region. SCyMark demonstrated adaptability and sustainability, promoting seamless integration between local offerings and digital marketing. The findings showcased significant shifts in stakeholders’ perceptions, with 23 out of 44 experiencing noteworthy changes in their perceived influence within the SCyMark framework. SNA offered intricate insights into stakeholder relationships, enhancing the study’s credibility. This research contributes valuable perspectives to regional development, highlighting SCyMark’s potential in promoting local products and events. By fostering community engagement and supporting economic growth, cyber marketing emerges as a promising tool for advancing marketing initiatives in diverse regions.